Comparison of Beluga (Huso huso) growth rate in brackish and fresh-water - Pourali Fashtami, H.R.; Mohseni, M.; Alizadeh, M. (2006)
Utilization of infertile coastal lands in the north Iran and Caspian Sea brackish water for reproduction and rearing of Beluga was the main objective of this study. To do so, 600 Huso huso fingerlings with an average weight of 48.29 grams were reared in fiberglass tanks (1.9*1.9*0.53m), amounting to 25 fish per square meter. We used a random statistical design in two trials under similar conditions (feeding rate, stocking density etc.) over a rearing period of 80 days. Brackish water was transferred from the Caspian Sea and used in four tanks (Group 1) and freshwater from the Sefidroud River was used in the remaining two tanks. Four replicates were used for experimental tanks and two were used for control tanks. Water flow in both groups was maintained at 0.2 to 0.5 liters per second. Results were analyzed statistically using one-way ANOVA and Duncan test. Mean water temperatures for brackish and freshwater treatments were 22.4±3.7 and 23.1±3.9 degrees centigrade respectively. Results of ANOVA on biometrical measurements during 71 rearing days indicated a significant difference in food conversion ratio (FCR) for the two treatments at 95% confidence level. After 71 days of rearing, FCR in Group I was 1.19±0.04, more suitable as compared to that in Group 2 (1.39±0.043). Fishes in Group 1 reached an average weight of 196.8g and those in Group 2 reached an average weight of 193.1g, indicating no significant difference in the final body weight of fishes in the two groups. Our observation showed better results for culture of Beluga in brackish water as compared to freshwater. Published